2012
DOI: 10.1080/10220461.2012.740180
|View full text |Cite
|
Sign up to set email alerts
|

The development of informal governance in post-apartheid South Africa: Criminal gangs as neo-medieval agents

Abstract: Employing international relations theory's concept of the new medievalism, this article applies a model of informal governance to the study of post-apartheid South Africa, arguing that what appear to be ungoverned spaces, criminality or corruption may in fact represent the development of informal governance. Employing a political-economy approach, it analyses the rise and decline of the modern state by reference to the relative efficiency of actors in the formal and informal systems. After an initial upsurge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In a similar vein, both Pattillo-McCoy (2000) and Venkatesh (2006), in their respective studies of African American Chicago street gangs, observed that gang leaders in middle-class Black areas policed disorder, graffiti, loitering, and fighting, along with addressing other public safety concerns. Rapley (2012) employed a political–economy approach to analyze the power of criminal gangs in post-Apartheid South Africa as agents able to supply services that the formal institutions were not equipped to provide in a period of state formation. Similarly, Lambrechts (2012) concentrated on the role of organized criminal groups with respect to local governance in the Cape Flats area of Cape Town.…”
Section: Problem Formulationmentioning
confidence: 99%
“…In a similar vein, both Pattillo-McCoy (2000) and Venkatesh (2006), in their respective studies of African American Chicago street gangs, observed that gang leaders in middle-class Black areas policed disorder, graffiti, loitering, and fighting, along with addressing other public safety concerns. Rapley (2012) employed a political–economy approach to analyze the power of criminal gangs in post-Apartheid South Africa as agents able to supply services that the formal institutions were not equipped to provide in a period of state formation. Similarly, Lambrechts (2012) concentrated on the role of organized criminal groups with respect to local governance in the Cape Flats area of Cape Town.…”
Section: Problem Formulationmentioning
confidence: 99%
“…[…] multiple and overlapping authorities co-exist; subordinate (to the central) authorities enjoy autonomous resource bases; these subordinate authorities can defend their autonomy but lack the power to fully secede from the system; and they exist in a relationship of reciprocal obligation with the central government, dependent on the latter for some services, while rendering services in return (Rapley, 2012).…”
Section: Conclusion: Rapley's Model -Hope and Historymentioning
confidence: 99%
“…This transformation however is incomplete (de Visser 2009). Studies point to increasing corruption, inefficient use of resources, poor service delivery and strong informal systems of rule and order (Rapley 2012;Hornberger 2010). This becomes more acute when dealing with mobile populations.…”
Section: Introductionmentioning
confidence: 99%